Sociodemographic factors’ influence on diarrheal diseases among children under five years in Kibish sub-county, Turkana, Kenya - Stephen, Ewoi E.; Lusire, Lumumba; Paul, Mutu L. (International Journal Of Community Medicine And Public Health, 2026)
Background: Diarrheal diseases are the third major causes of hospitalization, morbidity and mortality among children under five years in low and middle-income countries. In Kenya, during the year 2018, diarrheal cases among children under five years was 1,499,146. In the same year, Turkana County reported 16.5% diarrheal prevalence rate among children under five years, that suggest the diarrheal diseases are still a challenge. The aim of this study was to assess mitigation challenges on diarrheal diseases among children under five years in Kibish Sub-County, Turkana County. Methods: The study employed the precede-proceed model, and a mixed-methods research design was used. Target population of 2779 respondents participated in the study. The Yamane formula (1967) was used to determine a sample size of 354 respondents. The simple random sampling, cluster sampling and purposive sampling techniques were used. Results: The findings revealed that socio-demographic factors, such as household size and the number of children under five, were significant (p<0.014, p<0.0001). Environmental factors, like time spent fetching water, were also significant (p<0.01), as were behavioral factors, including handwashing after disposing of child feces and before feeding (p<0.021, p<0.029). These factors contributed to the prevalence of diarrheal diseases in the region. Conclusions: The study concluded that diarrheal diseases among children under five years in Kibish Sub- County, requires an integrated approach combining improved household size, WASH services, health education, timely treatment, nutrition support and stronger community-based health systems. The study recommended collaboration among stakeholders, promote household-level prevention measures, improve access to early treatment services, enhance community health education, strengthen water, sanitation and hygiene practices and improve healthcare infrastructure and staffing. Furthermore, the community leaders, stakeholders and community health promoters should design and implement targeted interventions that address the specific challenges experienced in Kibish Sub-County, including water scarcity, limited access to healthcare services, poor sanitation, immunization outreaches, and hygiene practices in order to curb diarrheal diseases.